Intermittent Price Changes in Production Plants: Empirical Evidence Using Monthly Data - Øivind Anti Nilsen; Magne Vange (Center for Economic Studies and ifo Institute (CESifo), 2018)
The price-setting behaviour of manufacturing plants is examined using a large panel of monthly surveyed plant- and product-specific prices. The sample shows a high frequency of zero changes, relatively small price changes, and a strong seasonal price-change pattern. The intermittent feature of price changes is modelled with thresholds which are smaller in January, and a quadratic loss function associated with the distance from the target price. The findings show statistically significant pricing thresholds, which are only two-thirds in January, and partial adjustment parameters implying that 60% of the deviation between the target price and the current price is closed each month.
Keywords: E30; E31; E37; 330; price setting; micro data; simulated method of moments